Anti-viral Effects of Pavetta indica Methanolic Extract and Acyclovir on Behavioral and Biochemical Parameters in Streptozotocin-induced Alzheimer's Disease in Rats - Kumar, Deepak; Singh, Govind; Tarun; Dhanawat, Meenakshi; Gupta, Sumeet; Morsy, Mohamed A.; B. Nair, Anroop; Matouk, Asmaa I. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: Alzheimer's disease is a neurological dysfunction of the brain caused by neurodegeneration and oxidative stress. Some viruses, such as herpes viruses, HSV-1, and HSV-2, are causative agents of Alzheimer's disease and result in β-amyloid peptide and tau protein accumulation in the brain. Some antiviral drugs, such as valacyclovir, acyclovir, and foscarnet, reduce amyloid-beta and P-tau. Pavetta indica leaves are also reported for their antiviral properties. The current study aimed to find out the significance of using Pavetta indica methanolic extract and acyclovir against Alzheimer's disease induced by streptozotocin. Methods: Wistar rats received acyclovir and Pavetta indica methanolic extract orally at different dose ranges (50, 150, 450 mg/kg) and (125, 250, 500 mg/kg), respectively. The standard therapy, Rivastigmine (2 mg/kg), was given orally. Results: Intracerebroventricular-streptozotocin produced significant alternations in behavioral assessments, including locomotor activity test, Morris water maze test, and elevated plus maze test. Moreover, intracerebroventricular-streptozotocin ameliorated the antioxidant defense activity by decreasing levels of catalase, superoxide dismutase, and reduced glutathione while enhancing the oxidative stress markers, including malondialdehyde, and total nitrite levels. Finally, the main findings showed that intracerebroventricular-streptozotocin significantly increased the inflammatory marker, tumor necrosis factor-α, and disturbed neurotransmitter mediators, including levels of acetylcholinesterase, glutamate, and γ-amino butyric acid. Conclusion: In a dose-dependent manner, acyclovir and Pavetta indica methanolic extract treatments abrogated the streptozotocin-induced behavioral and neurological abnormalities in rats. The potential therapeutic effects of PIME and acyclovir administration in intracerebroventricular-streptozotocin-treated rats may be attributed to its potential antiviral, antioxidant, and anti-inflammatory effects. The current study suggests that Pavetta indica methanolic extract and acyclovir are promising therapeutic targets against Alzheimer's disease.
Keywords: Pavetta indica